Pemenuhan Hak Asasi Politik Para Pemilih Pemula Pemilihan Umum Tahun 2024 Pada Warga Surabaya - Suryawati, Nany; Syahputri, Martika Dini (LPPM Institut Pendidikan Nusantara Global, 2024)
The 1945 Constitution of The Republic of Indonesia (UUD NRI 1945) Article 1 paragraph (2), states that sovereignty is in the hands of the people, which means that the Indonesian is a democratic country based on the constitution, because in paragraph (3) it is also said that Indonesia is a legal state. This popular sovereignty, especially in the political field, means that the people vote or elect their representatives to manage he government through general elections. It is reaffovured in article 1 paragraph (3) and article 2 paragraph (1) that MPR< DPR and DPRD are elected through general elections. Likewise in article 27 paragraph (2), article 28 paragraph (1), article 28 E paragraph (2) and article 28 I paragraph (5). Therefore, thus research uses empirical juridical research methods, because it is related to legal awareness among citizens, especaily regarding the use of voting rights in general elections as an effort to uncrease the number of votes in the upcoming 2024 general elections. Especailly for residents in one of the community unit in Klampisngasem sub-district, Sukolilo sub-district, Surabaya. The increasing number of prospective first-time voters since 2020 requires socializations regarding understands of voting rights so that citizens have legal awareness regarding voting rights as regulated in the 1945 NRI Constitution. This outreach s an effort to increase the number of first-time voters among citizens in the 2024 general elections. Increasing the number of first-time voters shows that the process of implementing the principles of democracy in Indonesia is in accordance with the 1945 Constitution of the Republic of Indonesia.